2018
DOI: 10.1038/s41388-018-0624-2
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon/IRF7 axis instigates chemotherapy-induced immunological dormancy in breast cancer

Abstract: Neoadjuvant and adjuvant chemotherapies provide survival benefits to breast cancer patients, in particular in estrogen receptor negative (ER − ) cancers, by reducing rates of recurrences. It is assumed that the benefits of (neo)adjuvant chemotherapy are due to the killing of disseminated, residual cancer cells, however, there is no formal evidence for it. Here, we provide experimental evidence that ER − breast cancer cells that survived high-dose Doxorubicin and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
118
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(129 citation statements)
references
References 51 publications
11
118
0
Order By: Relevance
“…Meanwhile, an association of human Tregs, neutrophils and inflammatory mediators such as interferon-gamma (IFNγ) are rather context-dependent [109]. With regards to the role of other interferons, a recent study demonstrated the role of IFN-β-induced immunological dormancy reflected in sustained activation of the IRF7/IFN-β/IFNAR axis in chemo-resistant (high dose doxorubicin and methotrexate) ER-negative 4T1 breast cancer cells in vitro and in vivo [110]. Meanwhile, one study to recapitulate sustained inflammation in lungs as demonstrated in smoker individuals revealed that neutrophil extracellular traps (NETs) proteases (elastase and MMP9) produced during inflammation can degrade laminin which further induces proliferation of dormant cells through activating αvβ3 integrin signaling, resulting in aggressive metastatic tumors in mice [111].…”
Section: Cancer Immune-mediated Dormancymentioning
confidence: 99%
“…Meanwhile, an association of human Tregs, neutrophils and inflammatory mediators such as interferon-gamma (IFNγ) are rather context-dependent [109]. With regards to the role of other interferons, a recent study demonstrated the role of IFN-β-induced immunological dormancy reflected in sustained activation of the IRF7/IFN-β/IFNAR axis in chemo-resistant (high dose doxorubicin and methotrexate) ER-negative 4T1 breast cancer cells in vitro and in vivo [110]. Meanwhile, one study to recapitulate sustained inflammation in lungs as demonstrated in smoker individuals revealed that neutrophil extracellular traps (NETs) proteases (elastase and MMP9) produced during inflammation can degrade laminin which further induces proliferation of dormant cells through activating αvβ3 integrin signaling, resulting in aggressive metastatic tumors in mice [111].…”
Section: Cancer Immune-mediated Dormancymentioning
confidence: 99%
“…It was recently demonstrated that chemotherapies elicit a state of immunological dormancy in ER-negative breast cancers, marked by sustained type-I IFN signaling, reduced cell growth, and longer progression-free survival(Lan et al, 2019). This indicates a possible shared mechanism between chemotherapy-induced immunological dormancy and ADAR1-dependency in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Upon dissemination in a secondary organ, metastatic breast cancer cells (BCCs) can undergo three fates: death, dormancy, or growth. Dormancy does not have a clear biological definition, it has been proposed a classification of dormant phenotypes into cellular dormancy (entering into reversible quiescence in G0) and tumor mass dormancy (a small cluster of cells where proliferation is counterbalanced by apoptosis due to lack of nutrients, blood supply or because of immune surveillance) (Linde et al, 2016;Goddard et al, 2018;Weidenfeld and Barkan, 2018;Lan et al, 2019). However, these states are likely to coexist within the same patients and probably the same cells can dynamically fluctuate between these different states.…”
Section: Metastatic Dormancymentioning
confidence: 99%
“…To distinguish between quiescence and senescence (or even apoptosis), cells must re-enter the proliferative state upon withdrawal of the factors used to trigger dormancy or upon treatment with signals able to drive exit from dormancy. Examples of such signals for BCCs are inflammation (LPS, smoke) (Cock et al, 2016;Albrengues et al, 2018), POSTN , TGFβ1 (Ghajar et al, 2013), RTKs (Tivari et al, 2015;, IL6, Collagen I (Barkan et al, 2010), Src (Barkan et al, 2010;, SFRP2 , IKKβ (Lamiaa et al, 2017), integrins activation (as discussed below); while examples of inhibitors are: TSP1 (Ghajar et al, 2013), p38 (Marlow et al, 2013), Alk5 (Marlow et al, 2013), BMP2 (Gao et al, 2012), TGFβ2 (Bragado et al, 2013), MSK1 (Gawrzak et al, 2018), IFN-β (Lan et al, 2019).…”
Section: Reversible Quiescencementioning
confidence: 99%